Candidemia in an Orthopedic Patient Detected Coincidentally by Peripheral Blood Smear - Eirini Spatha; Loredana-Mariana Gheorghe; Ioulia Chaliori; Nikolaos J. Tsagarakis; Nikolaos Patsiogiannis; Sofia K. Chaniotaki (Diagnostics)
An elderly male, with a recent COVID-19 infection and cardiovascular comorbidities, experienced a prolonged hospitalization due to a periprosthetic joint infection (PJI) and bacteremia, post hip hemiarthroplasty. Despite the initial clinical improvement while on targeted antimicrobial therapy, the patient later developed a low-grade fever and signs of myelosuppression. In the May–Grünwald–Giemsa stain of peripheral blood smear (PBS), pseudohyphae among red blood cells (RBCs) and phagocytosed blastospores in neutrophils and monocytes were detected, indicating candidemia rather than contamination of the stain. Echinocandin treatment was immediately initiated, and Candida albicans was identified from the blood culture, using multiplex polymerase chain reaction (PCR). Despite the early initiation of antifungal therapy and the removal of the central venous line (CVL), the patient passed away within 24 h. Candidemia is a leading cause of nosocomial bloodstream infections with high morbidity and mortality and is associated with multiple risk factors including surgery, CVLs, prolonged hospitalization, concomitant bacterial infection, broad-spectrum antibiotics, and immunosuppression. Isolation from blood cultures remains the gold standard for diagnosing candidemia. Detection of candidemia by PBS is extremely rare, requires an experienced microscopist, and is considered to be an emergency. Clinical suspicion, early laboratory identification, and immediate clinician notification are crucial for prompt antifungal treatment.